Pengaruh Pendidikan dan Penghasilan Keluarga terhadap Stunting pada Balita - Khotimah, Husnul (Prodi DIII Kebidanan La Tansa Mashiro, 2023)
Stunting is still a big challenge faced by this nation even in the world even though it can actually be prevented. This study aims to determine the socio-economic relationship (mother's education, father's education, family income) to the incidence of stunting. The design of this study uses a cross-sectional approach. The sample in this study were 100 toddlers. The sampling technique is purposive sampling. Data analysis using chi square. The results showed that there was a significant relationship between mother's education (p=0.003) and father's education (p=0.045) and the incidence of stunting in toddlers, but there was no significant relationship between family income (p=0.678) and the incidence of stunting in toddlers. There is a need for structured and continuous education to increase public knowledge about stunting.